The philosophy of Husserl - Hopkins, Burt C. (Continental European philosophy., 2011)
As the founder of phenomenology, Edmund Husserl has been hugely influential in the development of contemporary continental philosophy. In The Philosophy of Husserl, Burt Hopkins shows that the unity of Husserl's philosophical enterprise is found in the investigation of the origins of cognition, being, meaning, and ultimately philosophy itself. Hopkins challenges the prevailing view that Husserl's late turn to history is inconsistent with his earlier attempts to establish phenomenology as a pure science and also the view of Heidegger and Derrida, that the limits of transcendental phenomenology are historically driven by ancient Greek philosophy.